Using Four Types Of Notches For Comparison Between Chezy’s Constant(C) And Manning’s Constant (N) - Joyce, Edwin Bategeleza; Deepak, Tirumishi Jada; Eric, L.W.K; Munir, H. K. (2015)
In this technical paper, Chezy’s and Manning’s constant were compared, using four different notches on the plain bed. The first phase of this paper involves designing of the notches, using Auto Cad software followed by fabrication. The second phase involves carrying out Experiments in open channel Laboratory by using hydraulic bench. The final phase involves calculations of Chezy’s and manning’s constants. It was seen that, Chezy’s constant is directly proportional to actual discharge While Manning’s constant in inversely proportional to actual discharge. Chezy’s constant has higher value compared to Manning’s constant value. Also Manning’s Standard deviation is smaller compared to that of Chezy’s. This indicates the accuracy of the resistance coefficient due to the fact that the smaller the value of standard deviation the higher the level of accuracy. Therefore, the coefficient of resistance is more adaptable, simple and accurate in Manning’s constant